Loaded delta-hemolysin shapes the properties of Staphylococcus aureus membrane vesicles - Chen, Juan; Lv, Yuhuan; Shang, Weilong; Yang, Yi; Wang, Yuting; Hu, Zhen; Huang, Xiaonan; Zhang, Rong; Yuan, Jizhen; Huang, Jingbin; Rao, Xiancai (Frontiers in Microbiology, 2023)
Background Membrane vesicles (MVs) are nanoscale vesicular structures produced by bacteria during their growth in vitro and in vivo. Some bacterial components can be loaded in bacterial MVs, but the roles of the loaded MV molecules are unclear. Methods MVs of Staphylococcus aureus RN4220 and its derivatives were prepared. Dynamic light scattering analysis was used to evaluate the size distribution, and 4D-label-free liquid chromatography–tandem mass spectrometry analysis was performed to detect protein composition in the MVs. The site-mutation S. aureus RN4220-Δhld and agrA deletion mutant RN4220-ΔagrA were generated via allelic replacement strategies. A hemolysis assay was performed with rabbit red blood cells. CCK-8 and lactate dehydrogenase release assays were used to determine the cytotoxicity of S. aureus MVs against RAW264.7 macrophages. The serum levels of inflammatory factors such as IL-6, IL-1β, and TNFα in mice treated with S. aureus MVs were detected with an enzyme-linked immunosorbent assay kit. Results Delta-hemolysin (Hld) was identified as a major loaded factor in S. aureus MVs. Further study showed that Hld could promote the production of staphylococcal MVs with smaller sizes. Loaded Hld affected the diversity of loaded proteins in MVs of S. aureus RN4220. Hld resulted in decreased protein diversity in MVs of S. aureus. Site-mutation (RN4220-Δhld) and agrA deletion (RN4220-ΔagrA) mutants produced MVs (ΔhldMVs and ΔagrAMVs) with a greater number of bacterial proteins than those derived from wild-type RN4220 (wtMVs). Moreover, Hld contributed to the hemolytic activity of wtMVs. Hld-loaded wtMVs were cytotoxic to macrophage RAW264.7 cells and could stimulate the production of inflammatory factor IL-6 in vivo. Conclusion This study presented that Hld was a major loaded factor in S. aureus MVs, and the loaded Hld played vital roles in the MV-property modification.